Effect of Tertiary Amines on the Hydrolysis Kinetics of Benzoyl Chloride in Water-Dioxane Solutions - A. Batiha, Mohammad; A. Chizhova, Elena; M. Batiha, Marwan (Asian Journal of Chemistry, 2013)
The main object of this study was to study the effect of pyridine, 2-methyl pyridine, 3-methyl pyridine, 2,6-dimethyl pyridine, quinoline and tribenzylamine on the hydrolysis kinetics of benzoyl chloride in water-dioxane solutions. The investigation has been made by means of gas-liquid chromatography measurements. Almost equal rate constants have been determined for the hydrolysis reaction of benzoyl chloride in dioxane solutions. The catalytic effect of the studied range of tertiary amines on the hydrolysis reaction of benzoyl chloride was determined.